2019
DOI: 10.1016/j.respol.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Is this time different? How digitalization influences job creation and destruction

Abstract: With the process of digitalization now in full swing, many are wondering how the adoption of new technologies influences job creation and destruction. Much hinges upon the specific tasks that machines take on and how many new tasks are created through the adoption of new digital technologies. Some argue that most tasks that are at risk of automation are those performed by rather low-to medium-skilled employees, while most new tasks that emerge from the adoption of digital technologies complement high-skilled l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(158 citation statements)
references
References 30 publications
7
145
0
6
Order By: Relevance
“…In this article, digitalization is approached especially from the perspective of how it may change work and learning in the future. There are several analyses of how digitalization, and especially automation, alters job skill demands and the labor market (e.g., Autor et al 2003;Balsmeier and Woerter 2019;Frey and Osborne 2013;Muro et al 2017). Digitalization is associated with increased employment of especially high-skilled labor (e.g., Balsmeier and Woerter 2019; Frey and Osborne 2013).…”
Section: Digitalization Of Workmentioning
confidence: 99%
“…In this article, digitalization is approached especially from the perspective of how it may change work and learning in the future. There are several analyses of how digitalization, and especially automation, alters job skill demands and the labor market (e.g., Autor et al 2003;Balsmeier and Woerter 2019;Frey and Osborne 2013;Muro et al 2017). Digitalization is associated with increased employment of especially high-skilled labor (e.g., Balsmeier and Woerter 2019; Frey and Osborne 2013).…”
Section: Digitalization Of Workmentioning
confidence: 99%
“…Balsmeier conducted a survey in Switzerland reflecting higher outlay in digital development tends to lead to a greater proportion of highly skilled workers versus a lower proportion of low or unskilled ones (Balsmeier, 2019). This study has shown that online students have a significantly greater chance of finding remote global employment for highly skilled candidates with a better education.…”
Section: -285mentioning
confidence: 91%
“…In 2013 Rifkin brings to light, "This gives machine-based digital technologies their disruptive power, and it is these technologies in particular that are supposed to drive the current industrial revolution" (qtd. in Balsmeier, 2019).…”
Section: -285mentioning
confidence: 99%
“…If, in addition to the replacement of the local jobs, the needed (IT) services are outsourced and the company capital is located outside the region, there is no prospective benefit for the location where the land and infrastructure are actually engaged. This is a case of a combination of the highest exposure and the lowest adaptive capacity, as especially lower qualified groups of employees have potentially the lowest capability of professional reorientation [73]. • Adaptation to and shaping a new regional labour market:…”
Section: Loss Of Jobs In the Most Vulnerable Municipalitiesmentioning
confidence: 99%